DESIGN, SYNTHESIS, AND BIOLOGICAL EVALUATION OF GABAAR SUBTYPE SELECTIVE (α6, α2/3, AND α5) LIGANDS TO TREAT MIGRAINE, NEUROPATHIC PAIN, TRIGEMINAL PAIN, TOURETTE SYNDROME, EPILEPSY, ANXIETY AND COGNITIVE DISORDERS AS WELL AS ASTHMA - (:unkn) unknown (My University, 2023)
Part I: Development of α6-GABAAR Subtype-Selective Pyrazoloquinolinones for Treating Tourette Syndrome, Migraine, and Trigeminal PainThe α6β2/3γ2 GABAAR selective ligands have the potential for treating trigeminal orofacial pain and neuropsychiatric disorders with sensori-motor gating deficits. The positive allosteric modulators (PAMs) specifically targeting α6GABAARs hold promise as effective interventions for treating essential tremor (ET). A number of α6β2/3γ2 GABAAR selective pyrazoloquinolinones were synthesized and extensively studied. The deuterated pyrazoloquinolinone DK-I-56-1 emerged as the lead compound with significantly improved pharmacokinetics. Importantly, the ligands modulated diazepam-insensitive α6β2/3γ2 GABAARs, displaying no sedation and were not cytotoxic. PZ-II-029 and DK-I-56-1 demonstrate the ability to mitigate the motor-impairing effects caused by diazepam. These effects were moderately mitigated by DS-I-78. The α6GABAAR-selective PAMs DK-I-56-1, PZ-II-029, and LAU 463 significantly attenuated action tremor and restored physical well-being in a mouse model mimicking ET by acting in the cerebellum.
Part-II: The Development of a Scalable Synthesis, and Assessment of Bioactivity of Imidazodiazepines Targeting α2/3-GABAAR Subtypes for the Treatment of Epilepsy, Anxiety, and Neuropathic Pain KRM-II-81 is an imidazodiazepine that acts as a potentiator for GABAA receptors. It is currently in preparation for clinical development, showing potential for targeted modulation of receptor activity. It demonstrates widespread effectiveness in preventing seizures and is associated with minimal sedative effects. We outlined an innovative, revised, and refined synthetic pathway for KRM-II-81 suitable for the large-scale production of kilogram quantities of the compound. The recent biological and chemical findings represent crucial advancements in the progress of KRM-II-81 for individuals facing treatment-resistant epilepsy. These developments offer hope for improving the condition of patients who have not responded well to conventional treatments. A brominated analog, DS-II-73 , was synthesized and pharmacologically characterized as a potential back-up compound as KRM-II-81 moves forward into development. The synthesis from 2-amino-5-bromophenyl)(pyridin-2yl)methanone was processed in five steps with an overall yield of 38% and without the need for a palladium catalyst. GABAAR binding occurred with a Ki of 150 nM and only 3 of 41 screened binding sites produced inhibition > 50% at 10 mM and the potency to induce cytotoxicity was > 240 mM. DS-II-73 was selective for α2/3/5- over that of a1-containing GABAARs. Oral exposure of plasma and brain of rats was more than sufficient to functionally impact GABAARs. Tonic convulsions in mice and lethality induced by pentylenetetrazol were suppressed by DS-II-73 after oral administration and latencies to clonic and tonic seizures were prolonged. Cortical slice preparations from a patient with pharmacoresistant epilepsy (mesial temporal lobe) showed decreases in the frequency of local field potentials by DS-II-73. As with KRM-II-81, the sedative liabilities of DS-II-73 were low compared to diazepam. Molecular docking studies of DS-II-73 with the α1β3γ2L configured GABAAR showed low interaction with a1His102 that is suggested as a potential molecular mechanism for its low sedative side effects. These findings support the viability of DS-II-73 as a back-up molecule for its ethynyl analog, KRM-II-81, with the human tissue data providing translational credibility.
Part-III: The Design and Synthesis of Chiral α5 Subtype BzR/GABAAR Modulators for Treating Anxiety, Depression, and Schizophrenia as well as Asthma Gamma (γ)-amino butyric acid is a natural neurotransmitter with inhibitory functions in the brain. Benzodiazepines bind to specific subunits of GABA receptors, influencing brain activities. Different subunits contribute to various effects like sedation, anxiolysis, and cognition. Dysfunctional GABA receptors relate to CNS disorders. The search for improved treatments for anxiety, depression, and cognitive issues is vital. A series of α5-preferring ligands, including GL-II-73, were synthesized to address these needs. GL-II-73 showed promise in anxiolytic, antidepressant, and cognitive effects. A scalable synthesis method was developed and synthesized more than 40 grams for evaluation. Further studies are ongoing by DAMONA PHARMACEUTICALS to move this ligand toward the clinic for depression and potentially Alzheimer's disease. The α5-GABAAR subtype selective ligand MP-III-022, a monomethyl amide, is active in low doses in several psychiatric disorders including autism, antipsychotic activity, and cognitive disorders. MP-III-022 resulted in a reduction in slow wave power in mice with Angelman syndrome. Due to the results obtained with GL-II-73 and MP-III-022 in animal models, several analogs were synthesized to extend the structure–activity relationship and screened for pro-cognitive efficacy in Y-maze assay. GL-II-73 is the best ligand till date for this project. The α5-selective ligand MIDD0301 (GL-II-93) is currently in development by PANTHERICS for asthma treatment. Notably, this lead compound, MIDD0301, demonstrates relaxation effects on human, guinea pig, and mouse airway smooth muscle (ASM) in ex vivo studies. The imine migrated MIDD0301 known as MYM-III-100 showed better activity in guinea pig airway smooth muscle (ASM) ex vivo studies. Several analogs were synthesized based on the structures of MIDD0301, MYM-III-100, and evaluated on ASM assay. Several analogs including DS-II-67 showed better ASM relaxation profiles than MIDD0301 in the ex vivo ASM relaxation assay. The recently developed ligands need additional testing to fully characterize their profiles and assess whether they hold advantages over MIDD0301 for treating asthma. Further evaluation is necessary to determine their potential efficacy and safety in comparison to the established lead compound.
Keywords: DK-I-56-1; DS-II-67; DS-II-73; GABAA; GL-II-73; KRM-II-81